Similarities and Differences of Vascular Calcification in Diabetes and Chronic Kidney Disease - Wang X; Wang Z; He J (Diabetes, Metabolic Syndrome and Obesity, 2024)
Xiabo Wang,1 Zhongqun Wang,1 Jianqiang He2 1Department of Cardiology, Affiliated Hospital of Jiangsu University, Zhenjiang, 212001, People’s Republic of China; 2Department of Nephrology, Affiliated Hospital of Jiangsu University, Zhenjiang, 212001, People’s Republic of ChinaCorrespondence: Jianqiang He, Department of Nephrology, Affiliated Hospital of Jiangsu University, Zhenjiang, 212001, People’s Republic of China, Email hejq0305@163.com Zhongqun Wang, Department of Cardiology, Affiliated Hospital of Jiangsu University, Zhenjiang, 212001, People’s Republic of China, Email wangtsmc@126.com; wangzhongqun@ujs.edu.cnAbstract: Presently, the mechanism of occurrence and development of vascular calcification (VC) is not fully understood; a range of evidence suggests a positive association between diabetes mellitus (DM) and VC. Furthermore, the increasing burden of central vascular disease in patients with chronic kidney disease (CKD) may be due, at least in part, to VC. In this review, we will review recent advances in the mechanisms of VC in the context of CKD and diabetes. The study further unveiled that VC is induced through the stimulation of pro-inflammatory factors, which in turn impairs endothelial function and triggers similar mechanisms in both disease contexts. Notably, hyperglycemia was identified as the distinctive mechanism driving calcification in DM. Conversely, in CKD, calcification is facilitated by mechanisms including mineral metabolism imbalance and the presence of uremic toxins. Additionally, we underscore the significance of investigating vascular alterations and newly identified molecular pathways as potential avenues for therapeutic intervention. Keywords: chronic kidney disease, vascular calcification, diabetes mellitus